Alcoholismo y su influencia en la funcionalidad familiar en el sector Chontacruz Alto Barrio La Palmera cantón Loja. - Ojeda Viñamagua, Diana Margarita (2016)
The alcohol consumption is liked to many social problems and development, especially violence, negled and child abuse and absenteeism; in particular it has a great influence on family functioning. This research aims to establish the alcoholism influence on family function, in Chontacruz high neighboardhood. La Palmera Loja Parish. To analize the level of alcohol consumption, determine the type og family functioning and identify the most affected marital status by alcoholism. It`s performed under a descriptive, quantitative approach and cross section. The Disorders identification test is used for drinking (AUDIT) and perception test of family functioning. The amalizec sample corresponds to 60 people who belong Chontacruz high neighboardhood La Palmera Loja parish, also they were chosen under inclusion criterion. As results, we can demostrate through chi-cuadrado that there is a short relation between alcohol influence and family functioning, 77,4% of people are married who have family problems, also tree relationship single and widow 66,7% are moderated functional families, followed functional families, strong dysfunctional families and disfuntional family, 50% of the families that consum alcohol must receive a conference about dangerous effect of alcoholism. In conclusion we can note that the alcoholism influences on the family functionality so it`s urgency to work on primary family attention to keep the emocional balance between families. Keywords: Alcoholism, family functionality.